PENCEGAHAN PERKAWINAN DI USIA MUDA DI KABUPATEN JOMBANG : ( STUDI ANALISIS PUTUSAN PENGADILAN AGAMA JOMBANG NOMOR 198/Pdt.P/2021/PA.Jbg) - Sayyid Jamaluddin Al Husaini Al Af; Muhammad Andri (Fakultas Hukum Universitas Darul Ulum, 2023)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on Belief in One Almighty God. Young or early age marriage is a marriage that is carried out when they are not yet 20 years old, both male and female. So that this age becomes one of the obstacles for himself, his family and society to achieve a good life stability. Based on the provisions of Law Number 16 of 2019 it states that marriage is only permitted if a man and a woman have reached the age of 19, whereas in the previous Law No. 1 of 1974 the minimum age for marriage for women was 16 years and for men 19 years old. From underage marriages there are several social problems faced, including promiscuity due to lack of control and effective communication from parents, economic factors, low education factors, cultural and traditional factors, and mass media factors. The fact is that the implementation of marriage at an early age has a negative impact on children, both physically and mentally. Based on the Study Report on Child Marriage in Indonesia, high rates of early marriage can increase the risk of death for mothers and children. Some examples of impacts that can result from early marriage include health problems, the risk of babies born with stunting, hampered education, and inharmonious marriages. Early marriage will certainly lead to underage work because like it or not, early age couples have to make a living for their next life. Because they are underage, of course finding a job will be difficult, this will result in economic difficulties and in the long term, child neglect. In other words, underage marriage can be contrary to the objectives of Islamic law and therefore the Jombang Religious Court prevents underage child marriages in Jombang Regency.